Deployment Porosity Estimation of Sandstone Reservoir in The Field of Hidrocarbon Exploration Penobscot Canada - Himmah Khasanah; Puguh Hiskiawan; Supriyadi Supriyadi (UPT Penerbitan Universitas Jember, 2016)
Porosity is defined as the percentage of empty spaces for storing fluid contained in rock.. Porosity becomes one of the requirements for determining reservoir which is good or bad. Porosity can be obtained from the seismic data has been acquired and processed previously; to obtain porosity from seismic data it is necessary determine an acoustic impedance value first. Acoustic impedance and porosity can be obtained by using deterministic inversion and neural network. Deterministic inversion operates in minimizing the difference between the acoustic impedance inversion results with the original. Deterministic inversion is part of the model-based inversion. The result of the inversion showed a correlation of 0.8 on a scale of 0-1. This result can be categorized a good inversion. Then acoustic impedance volume converted into volume porosity by using neural network. Neural network method showed a value of 0.2 for the difference between the acoustic impedance volume and volume porosity. The result of deterministic inversion and neural network method were the value of the distribution of porosity in the reservoir sandstone ranges from 13% to 23%.